Sex- and gender-related differences in inflammatory bowel diseases - Blumenstein, Irina; Sonnenberg, Elena (Frontiers in Gastroenterology, 2023)
This review provides an overview on the current data regarding sex- and gender specific aspects in patients suffering from inflammatory bowel diseases. A particular focus will be on disease course, medical as well as surgical treatment strategies, psychosocial differences and on the special requirements during pregnancy and family planning. The most significant and clinically meaningful gender differences in IBD relate to psychosocial functioning. Although depression, fatigue, anxiety disorders, eating disorders and sexual dysfunction also occur in male IBD patients, women seem to be affected much more frequently and severely in this area.